2016
DOI: 10.3144/expresspolymlett.2016.95
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of 4-methyl-1-pentene with α,ω-alkenols

Abstract: Abstract. Copolymerization of 4-methyl-1-pentene (4M1P) with 9-decen-1-ol (9D1O) or 4-penten-1-ol (4P1O) was conducted by using metallocene catalysts. The activity could be improved under the higher polymerization temperature. The dyad distribution of poly(4M1P-co-4P1O) was presented. The results showed that 4P1O was uniformly distributed in the copolymer chain. The melting temperature (T m ) of the copolymer was lower than that of poly(4M1P), and was decreased with the increase of the incorporation of comonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Previously, we studied the comonomer effects for olefin copolymerization by using metallocene and half‐metallocene catalyst systems. We concluded that the structure of the comonomer strongly influenced the polymerization activity and the microstructure of the resulted polymer . In the copolymerization of ethylene with α,ω‐alkenols, the length of the alkenol monomer strongly impacts on the microstructure of the copolymer.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previously, we studied the comonomer effects for olefin copolymerization by using metallocene and half‐metallocene catalyst systems. We concluded that the structure of the comonomer strongly influenced the polymerization activity and the microstructure of the resulted polymer . In the copolymerization of ethylene with α,ω‐alkenols, the length of the alkenol monomer strongly impacts on the microstructure of the copolymer.…”
Section: Introductionmentioning
confidence: 92%
“…Alkenol with fewer methylene spacers trends to give the copolymer with more successive comonomer segments, at the same time, the structure of the copolymer obtained from the alkenol with the more methylene spacers is more random . Especially, we realized that the length and the structure of the comonomer give an important impact on the melting point and the stereoregularity of the polymer . Thus, we will explore more novel comonomers for copolymerization, intending to get new polymer with new chemical composition, and enrich the investigation of the comonomer effect.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in ECMO, which is used to treat severe COVID-19 patients, the hollow fibers of the oxygenator are made of PMP [12]. As a result, the (co)polymerization of 4-methyl-1-pentene (4M1P) has been extensively studied [13][14][15][16]. The isospecific polymerization of 4M1P can be carried out through the coordination polymerization of Cr-, V-, Ti-, and Zr-based catalysts, of which the titanium catalyst is the most commonly used [13].…”
Section: Introductionmentioning
confidence: 99%